Changes in maximal double poling performance during and after mderate altitude training in elite cross-country skiers - Höök, M.; Jensen, K.; Willis, S.; Holmberg, H. C. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
In 2014, the Olympic cross-country ski competitions will be held in Sochi, Russia at approximately 1500m altitude. Even moderate altitude can have negative effects on performance in highly trained endurance athletes and individuals may adapt and react differently to altitude exposure [1]. Different skiing techniques (such as double poling) may also be affected by altitude due to the involvement of the upper body. Thus, the purpose of our study was to evaluate changes in double poling performance during and after three weeks of training in moderate altitude in elite skiers. METHOD: Four male and three female skiers were tested on a roller skiing treadmill using the double poling technique at sea level (NORM1), after 3 and 20 days at 1500m altitude (ALT1 and ALT2), and 10 days after altitude at sea level (NORM2). A progressive "all out" double pooling test consisted of 4-7 min of exercise with an increase in speed and then grade every minute until exhaustion. Oxygen uptake (VO2) was measured continuously during maximal exercise and VO2peak was taken as the highest VO2 during exercise. Maximal blood lactate concentration was measured between 1 and 2 min after termination. Average power was calculated from roller ski friction and transported body mass against gravity [2]. RESULTS: At NORM1, the skiers` body mass was 73.9±11.6kg and VO2peak 200±21ml/min/kg0.73. Blood lactate accumulation after maximal exercise was 9.6±1.7mmol/l and showed no difference between conditions (P>0.05). No change in VO2peak was seen between NORM1 and NORM2. The VO 2peak increased 5.6% at NORM2 compared to ALT1 and ALT2 (P<0.05). In contrast, the average maximal power output at NORM1 (254±69W) increased 6.8% at ALT2 and NORM2 (P<0.05). No differences were found between NORM2 and ALT1 and ALT2. DISCUSSION: The current study demonstrated that in a group of elite skiers training at moderate altitude corresponding to 1500m, maximal double poling power is maintained and even increased during altitude. Furthermore, VO2peak was also increased when returning to sea level. These findings suggest that the anaerobic energy system is more involved in the double poling technique while at altitude than after return to sea level. However, this could not be confirmed by higher maximal blood lactate concentrations after exercise while at moderate altitude. CONCLUSION: Maximal double poling exercise in highly trained elite skiers seems to be less affected by moderate altitude indicating a greater dependence of the anaerobic energy system during upper body exercise.